Tahwīlu al-Ṣautiy wa al-Tarjamah Linaṣṣi “Kitābi al-Bayān” Kashaklin min Ashkāli al-Hifādz ‘Alā al-Thaqāfati al-Wathaniyah - Malia Fransisca (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
This research explains about preserve one of the manuscripts in the Sidoarjo Mpu Tantular Museum as a form of caring for the academic community in the fields of language and literature. Considering the explanation from the Head of the Mpu Tantular Museum Collection Section that more than 300 manuscripts in the Mpu Tantular Museum that have been translated or translated only about 9-10 manuscripts. If those was propagated only 3% has been translated. Therefore, we want to preserve the culture of the Indonesian people through the translation and transliteration of the “Kitab al-Bayan”. This research was conducted by students of the Arabic Language and Literature study program at the Sunan Giri Bojonegoro Islamic Institute in one month at the Mpu Tantular Museum. In one month there are 3 kinds of activities at the Mpu Tantular Museum. First, copy the manuscript again so that the “Kitab al-Bayan” has a soft copy that is not susceptible to time. Second, transcription or also called transliteration. Third, language transfer is better know as the translation of a text. The method was used in this study is analytical method. So in the prosess of copying back the manuscript, transliteration and translation will be analyzed both in terms of writing and the contents of the manuscript. Analysis in terms of writing with the aim of maintaining the physical script, while analysis in terms of content is a form of maintaining the content or quality of the manuscript. So the result of this study are in the form of copying Arabic texts, transliteration and translation of “Kitab al-Bayan”. Keywords : Translation, Transliteration, Manuscripts, Kitab al-Bayān.